Back to school during the COVID-19 pandemic: Mitigating risks while promoting individual and community well-being among children and adolescents at school re-entry. - Ngov, Cindy; Miconi, Diana; Papazian-Zohrabian, Garine; Rousseau, Cécile (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 2022)
The COVID-19 pandemic has called for unplanned school closures, leaving millions of children and adolescent confined for a prolonged period of time. Although many guidelines exist for the mitigation of viral transmission upon school re-entry, school-based interventions that can help alleviate the many other potentially long-lasting consequences of the current crisis on students have yet to be documented. Acknowledging mental health difficulties, educational and socioeconomic disparities, and intercommunity tensions is an essential part of supporting students, caregivers, and educators with the transition back to school. Open communication, psychological first aid interventions, capacity-building, and a response-to-intervention approach are key to mitigating the effects of the pandemic, as they are backed by evidence and implementable even in low-resource classrooms.